Seismic fragility analysis of hunchbacked gravity quay walls using a multi-intensity measure approach - Ali Akbar Ehterami; Babak Ebrahimian; Ali Noorzad (Results in Engineering)
This study investigates the seismic resilience of hunchbacked block-type gravity quay walls with different back-face geometries using the finite element method (FEM). Three hunchbacked block-type quay wall models, identified as QW-I, QW-II, and QW-III, each with a distinct geometrical configuration, are analyzed. The QW-I model represents the quay wall already built at the Pars Petrochemical Port in Asalouyeh, Iran, and serves as the reference case. Initially, the seismic response of these quay walls is evaluated under a range of seismic loads with varying dynamic characteristics. Subsequently, fragility curves are generated for the three wall configurations based on multiple intensity measures (IMs) to assess their vulnerabilities to seismic events. For this purpose, acceleration time histories derived from real earthquake records are utilized, with fragility assessments conducted using the incremental dynamic analysis (IDA) approach. The generated fragility curves demonstrate that increasing the hunch height from 3 m in QW-I to 5 m in QW-II and 6 m in QW-III significantly reduces the probability of exceeding the repairable damage level and reaching near collapse for a peak ground acceleration (PGA) of 0.51 g, comparable to that of the 1990 Manjil earthquake. Specifically, this probability decreases from 69.49 % for QW-I to 55.99 % for QW-II and 49.51 % for QW-III. Correspondingly, based on the cumulative absolute velocity (CAV) indicator, the exceedance probability drops from 21.75 % for QW-I to 11.22 % for QW-II and 7.88 % for QW-III. Therefore, the interpretation of seismic vulnerability and associated failure probabilities can vary depending on the chosen IM for fragility analysis, emphasizing the necessity for developing multi-valued fragility curves.